Does work commitment mediates the effect of Islamic work ethic on performance and turnover intention? - Miswanto Miswanto; Rois Arifin; Dwi Murniyati (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2020)
Islam is a comprehensive religion that covers not only the ritual worship aspect but also ethics and acts of business. The field of Islamic work ethics has been studied by many researchers in different study settings. However, the important role of Islamic work ethics has been underexplored in work commitment studies. Therefore, this study aims to examine the direct and indirect effect of Islamic work ethics in affecting employees work performance and turnover intention through work commitment. This study used the quantitative method as their main research design. Purposive sampling was applied as a sampling technique with a five-point Likert scale of the structured questionnaire as a measurement scale and data gathering method. The bootstrap method used to test the proposed hypotheses. This study concluded that Islamic work ethic positively affects work commitment, thus work commitment positively affects work performance. This study also found that there was an insignificant effect of Islamic work ethic on work performance and turnover intention, and work commitment on turnover intention. Fundamentally, the mediation role of work commitment failed to prove in this study as there were only significant indirect effects between Islamic work ethic and work performance. In other words, the higher individual beliefs on Islamic value, the more committed employee to do their job. Thus, the more committed and enthusiastic employees on their job, the higher their work performance will be.